Remarks at the Leaders’ Summit on Climate - Malpass, David (World Bank, Washington, DC, 2021)
David Malpass, President of the World Bank, discussed the core plan of the World Bank’s climate change action plan. The World Bank Group has reached its highest-ever levels of climate finance in the past two years. The Bank plan commits to big increases in spending, focused on results, plus active private sector mobilization through International Finance Corporation (IFC) and Multilateral Investment Guarantee Agency (MIGA), the private sector focused entities. Also, the Bank is aligning the financing flows with the Paris Agreement. The Bank goal is to provide support, and take prompt action, in ways that create the most positive impact toward green, resilient, and inclusive development.